Predictors of Tobacco Use among Medical Students of Ahvaz University: A Study Based on Theory of Planned Behavior - Marzieh Araban; Mohamood Karimy; Mohammad Taher; Sahar Baiati; Aliakbar Bakhtiari; Hamid Abrehdari; Neda Fayazi; Ahmadreza Abedi (Journal of Education and Community Health)
Background and Objectives: Tobacco use among medical students is important for the health of the general population since medical groups are important role models in terms of health related behaviors. Therefore, the objective of this study was to investigate tobacco use and its predictors among medical students of Ahavaz University based on the theory of planned behavior (TPB). Materials and Methods: A cross-sectional study using a self-administered questionnaire was conducted in 2014 among 170 medical students (56 males, 114 females), at Ahvaz University of Medical Sciences. Data were analyzed using SPSS version 18 software program. Logistic regression analysis was used to calculate the odds ratio (OR) and 95% confidence interval (95% CI) and to determine the effect of demographic factors and theory of planned behavior (TPB) constructs on students’ smoking behaviors. Results: From all subjects, 36% of boys and 3.5% of girls were current smokers. Using multiple logistic regression models, being male, having friends who smoke, smoking parents and smoking brother were strongly associated with tobacco use. Furthermore, all component of TPB, subjective norms, perceived behavioral control and intention were found to predict student’s smoking. Conclusion: The present study propose that subjective norms and selection of friends need to be considered as the most important factors explaining smoking behavior among medical students besides the TPB constructs.